Pengaruh Kualitas Pelayanan Dan Harga Terhadap Kepuasan Konsumen Pada Butik Simplyveewee Bintaro - Siti Nurazizah; RR.Renny Anggraini (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
The aim of this research is to determine the influence of service quality and price, both partially and simultaneously, on consumer satisfaction at the Simplyveewee Bintaro Boutique, with a sample of 99 consumers. The method used is a quantitative method. The data analysis used in this research is the classical assumption test, simple linear regression analysis, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, t test and F test. The results of this research are that Service Quality has a significant effect on Consumer Satisfaction in the regression Y = 3.045 + 0.908 Price has a significant effect on Consumer Satisfaction with the regression equation Y = 3.464 + 0.897 Service Quality and Price simultaneously have a significant effect on purchasing decisions with the regression equation Y = 2.388 + 0.373 X1 + 0.555 X2. The coefficient of determination value was 88.7%, while the remaining 11.3% was caused by other variables not examined in this research. The test results for the first hypothesis obtained a calculated t value > t table or (23.355 > 1.661). Based on the results of testing the second hypothesis, the t value obtained > t table or (25.591 > 1.661). Based on the results of testing the third hypothesis, the Fcount value was 378.481 > Ftable 3.091. This shows that simultaneously the Service Quality and Price variables have a significant influence on Consumer Satisfaction